Analisis Kausalitas Antara Konsumsi Energi Fosil, Pertumbuhan Ekonomi dan Foreign Direct Investment di Negara-Negara ASEAN - Maisa Mahran Rahmahhani; Siti Fatimah Zahra; Sri Indah Nikensari (Indo Publishing, 2026)
This study examines the causal relationship between fossil energy consumption, economic growth, and foreign direct investment (FDI) in six ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, Vietnam, and the Philippines) over the period 2005-2024. Using panel data with 120 observations, this research employs the Panel Vector Error Correction Model (PVECM) framework with ARDL Pooled Mean Group (PMG) estimation and Dumitrescu-Hurlin causality test integrated within the Toda-Yamamoto approach. The findings reveal unidirectional causality running from economic growth to fossil energy consumption at the 5% significance level, supporting the Conservation Hypothesis. Furthermore, unidirectional causality is found from fossil energy consumption to FDI and from economic growth to FDI at the 1% significance level, indicating that FDI acts as a pure recipient in the ASEAN causal system. In the long run, fossil energy consumption has a positive and significant effect on economic growth with an elasticity of 1.011 at the 1% level, while FDI shows a significant positive effect on fossil energy consumption with a coefficient of 0.039 at the 1% level. The Error Correction Term (ECT) is negative and significant at the 10% level in the energy equation, confirming a long-term equilibrium adjustment mechanism. These findings imply that economic growth is the primary driver in the ASEAN energy-investment system, while FDI does not provide significant feedback to either economic growth or energy consumption, suggesting the need for green investment attraction and energy diversification policies to achieve sustainable development in the region.